Human and economic losses caused by volcanism in Costa Rica from 1953 to 2005 - Aguilar, Irene (2014)
An integrated approximation of the impact of volcanic eruptions in the 20th century in Costa Rica is presented for the first time. The detailed damage (bridges, houses, railways, factories), economic losses (agriculture, livestock, drinking water), disruption of activities, loss of life and investments (donations, mitigation measurements), is given. This focuses on the disasters and economic effects, but the sociological and psychological effects were not assessed. Two national emergencies occurred with the eruption of Irazú in 1963-1965 and Arenal in 1968, and several volcanic crises occurred at other volcanoes including Poás (1953-1955, 1989-1994), Rincón de la Vieja (1967, 1991, 1995 and 1998), and again in Arenal (1975, 1988 and 2000), which produced economic losses due acid rain and/or lahars, and loss of life resulting from pyroclastic flows. More recently, phreatic and fumarolic activity at Turrialba volcano, which started in 2010, affected the surrounding area due to acid rain; however, there is no estimation of the economic losses for this activity. Volcanic activity is responsible for a loss of at least $48.7 million in the last century, quantity that is necessary scalar in a future study. In this century, the damage due acid rain is more than $200 million. It is certain that 103 people were killed by volcanic activity in the 20th century, and there are no additional reports of deaths or injuries since 1700. This paper is the basis for future work focused on the socio-economic evaluation, risk analyses and future projections. If a new eruption similar to those of Irazú in 1963-1965 or Arenal in 1968 were to happen during the present century, the economic losses can be expected to be larger than previous ones